Environmental Evidence - Pullin, Andrew
Environmental Evidence is the journal of the Collaboration for Environmental Evidence (CEE). The Journal facilitates rapid publication of evidence syntheses, in the form of Systematic Reviews and Maps conducted to CEE Guidelines and Standards. We focus on the effectiveness of environmental management interventions and the impact of human activities on the environment. Our scope covers all forms of environmental management and human impacts and therefore spans the natural and social sciences. Subjects include water security, agriculture, food security, forestry, fisheries, natural resource management, biodiversity conservation, climate change, ecosystem services, pollution, invasive species, environment and human wellbeing, sustainable energy use, soil management, environmental legislation, environmental education. Objective use of scientific evidence to inform policy or practice is a major aim and to that end the journal also publishes methodology papers and encourages submissions that promise advances in the field of evidence synthesis and dissemination. Discussion of wider issues surrounding the use or misuse of evidence in decision making are welcome in the form of commentary articles. Environmental management is now a mainstream political activity with major resources being committed to growing challenges related to climate change, natural resources, ecosystem services and human wellbeing. Despite the large and rapidly increasing amounts of primary environmental research, the potential of the data to address questions of concern to policy makers and managers has not been fully realised. CEE promotes and facilitates the conduct of systematic reviews and synthesis of evidence, and seeks to make this information more accessible to all through open access publishing.